Language Disorders in Autistic Students in Learning Arabic at Elementary School of Anak Shaleh Malang - Muhammad Qodri; Almu Padol (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2022)
This article aims to describe the types of autistic and language disorders experienced by autistic students, problems of learning arabic faced by autistic students and the teacher's efforts in overcoming problems caused by language disorders when learning Arabic. This article uses a descriptive qualitative approach. data collection through interviews, observation, documentation. Data collected were analyzed through the steps of data reduction, data presentation, drawing conclusions. The findings of this article are: (1) the types of autism and language disorders experienced were: Suffering from attention deficit hyperactivity disorder and autism with active group classification but rarely or called mild autism. Experiencing Autism with the type of Asperger's syndrome. Experiencing severe autism, the characteristics that appear in this student are having trouble communicating, he likes to be quiet with his own activities. (2) The problems in language disorders are: hard to get along and slow in receiving lesson information and Weak Academic Skills, Communication and Behavior. (3) the teacher’s endeavor to solve these problems, they are Take a different special approach, including by frequently communicating lightly. Collaborate between teachers. Provide full opportunities for GPK to assist and carry out therapy, both at home and at school.